High prevalence of adenomatous colorectal polyps in young cancer survivors treated with abdominal radiation therapy: results of a prospective trial. Issue 10 (13th July 2016) - Daly, Patricia E; Samiee, Sara; Cino, Maria; Gryfe, Robert; Pollett, Aaron; Ng, Andrea; Constine, Louis S; Hodgson, David C
Abstract : Objective: Cancer survivors treated with abdominal/pelvic radiation therapy (ART) have increased the risks of colorectal cancer (CRC), although evidence supporting early CRC screening for these patients is lacking. We sought to determine whether there is an elevated prevalence of adenomatous colorectal polyps in young survivors prior to the age when screening would be routinely recommended. Design: We conducted a prospective study of early colonoscopic screening in cancer survivors aged 35–49 who had received ART ≥10 years previously. The planned sample size was based on prior studies reporting a prevalence of adenomatous polyps of approximately 20% among the average-risk population ≥50 years of age, in contrast to ≤10% among those average-risk people aged 40–50 years, for whom screening is not routinely recommended. Results: Colonoscopy was performed in 54 survivors, at a median age of 45 years (range 36–49) and after median interval from radiation treatment of 19 years (10.6–43.5). Forty-nine polyps were detected in 24 patients, with 15 patients (27.8%; 95% CI 17.6% to 40.9%) having potentially precancerous polyps. Fifty-three per cent of polyps were within or at the edge of the prior ART fields. Conclusions: Young survivors treated with ART have a polyp prevalence comparable with the average-risk population aged ≥50 years and substantially higher than previously reported for the average-risk population aged 40–50 years. These findings lend support to the early initiation of screening in these survivors. Clinical trial registration number: NCT00982059; results.